Premorbid Alterations of Spontaneous Brain Activity in Elderly Patients With Early Post-operative Cognitive Dysfunction: A Pilot Resting-State Functional MRI Study - Zhang, Xixue; Li, Hui; Lv, Yating; Zhu, Zhenghong; Shen, Xiaoyong; Lu, Qi; Wang, Wei; Wang, Zhaoxin; Jiang, Zhaoshun; Yang, Lvjun; Lin, Guangwu; Gu, Weidong (Frontiers in Neurology, 2019)
Background: Elderly patients with preexisting cognitive impairment are susceptible to postoperative cognitive dysfunction (POCD). In this study, we investigated whether there is preexisting local homogeneity and functional connectivity alteration in the brain before surgery for POCD patients as compared to that in non-POCD patients. Methods: Eighty elderly patients undergoing major thoracic or abdominal surgeries were recruited. Resting-state functional MRI was scanned at least 1 day before surgery. Neuropsychological tests (NPTs) were performed before surgery and at discharge, respectively. Preoperative regional homogeneity (ReHo) and resting-state functional connectivity (RSFC) were compared between POCD patients and non-POCD patients, respectively. Partial correlation between NPTs and ReHo or RSFC was analyzed by adjusting for confounding factors. Results Significant difference (P < 0.001, Gaussian Random Field (GRF) correction which is a multiple comparisons correction method at cluster level, cluster size > 49) in ReHo between POCD patients and non-POCD patients was detected in right hippocampus/parahippocampus. Preoperative RSFC between right hippocampus/parahippocampus and right middle/inferior temporal gyrus increased in POCD patients (P < 0.001, GRF correction for multiple comparisons) when compared with that in non-POCD patients. RSFC significantly correlated with composite Z-score (r = 0.46, 95%CI [0.234, 0.767], P = 0.002) or Digit Symbol Substitution Test Z-score (r = 0.31, 95%CI [0.068, 0.643], P = 0.046) after adjusting for confounding factors. Conclusions The results suggest that premorbid alterations of spontaneous brain activity might exist in elderly patients who develop early POCD. The neural mechanism by which patients with preoperative abnormal spontaneous activity are susceptible to POCD remains further study.